Prevalence and mortality from diabetes in Cuba during the 2010-2019 decade - Moura Revueltas Aguero; Maritza Benítez Martínez; Enrique Molina Esquivel; María del Carmen Hinojosa Álvarez; Silvia Venero Fernández; Mariela Hernández Sánchez (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: Diabetes is a serious and chronic condition that occurs when a person's blood glucose levels are high because the body cannot produce insulin or its amount is insufficient. It is an important and independent risk factor for cardiovascular diseases and other damages. Objective: To describe the prevalence and mortality from diabetes in Cuba during the decade 2010-2019. Material and Methods: A descriptive ecological study on diabetes in Cuba was carried out. Dispensarization and gross mortality rates due to the disease in the 2010-2019 decade were taken into account. The statistical yearbooks published by the Directorate of Medical Records and Health Statistics of the Ministry of Public Health those years were used as a source of information. Results: The prevalence of diabetes in Cuba in the decade tended to increase from 4,04 % in 2010, to 6,67 % in 2019. It was more frequent in women. Crude mortality rates decreased in that period from 23,9 to 20,6 per 100 000 inhabitants. Conclusions: The annual prevalence rates of diabetes reported in Cuba were higher in females. In the decade, the general prevalence of diabetes showed an increase, while the trend in gross mortality from this disease was related to the decrease. Women were more likely to die than men.